Versuch der Analyse des Vertrags von Lissabon nach dem Mehrebenenmodell von Heinemann/Heinemann - Woźniak, Joanna (Wydawnictwo Rys, 2014)
This paper discusses the issue of multilevel text classification by Heinemann/Heinemann. In particular it aims to analyse the Lisbon Treaty on the European Union considering its function in communication, the type of situation, in which it is used, type of communicative strategy, its structure and some stereotypical formulations that are distinctive for this type of text.
Keywords: analiza tekstu; konwencjonalizacja tekstu